Pengembangan Modul Self-Management untuk Mengurangi Perilaku Merokok - Rafifah, Rafifah; Nurbaity, Nurbaity; Fajriani, Fajriani (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2022)
Smoking behavior, especially in adolescents or students, needs to be treated to reduce smoking behavior. In this situation, one way that can be done is with the help of a selfmanagement strategy. Self-management serves to manage themselves or regulate the behavior of the students themselves. This study aims to develop a learning media in the form of a self management module that is suitable for use byeducators as teaching materials. The approach used in this research is mixed methods. The type of research used in this research is research and development method. The subjects in this study were material experts and media experts. The data collection tool usedis a validation sheet to obtain an assessment from the validator. Product validation to two material experts which resulted in a conclusion with a feasible category and from a media expert to produce findings in a very feasible category.